(untitled) (Fiep Bulletin - online, 2015)
The proposal to the schooling physical education elabored by Brazil. MEC (1998), get like physical education’s knowledgement the human being in movement using as contents games, sports, dances, gymnastics and fights in the conceptual, attitudinal and proceedings dimentions that must guarantee to the students the opportunities to access and enjoy the body culture. This research used the descriptive method with objective of identify the contents developed in schooling physical education in the cities of Great São Paulo and analyze the utility of them to the high school students present and future life, in their own conception. Using like tool of collect data an open questionnaire composed by five questions, applied to a sample of 813 teenagers (16-23 year old), box sex, from public and private schools, asking about their participation in the schooling physical education; which activities were developed; the benefits of them; the class learnings and it’s importance to their future. The results showed that 84% of the students participate in the most of the classes, the experienced contents was 72% sports, 22% gymnastics, 11% games, 0,6% dances, 0,4 fights and 45% learned new sports. The mentioned benefits by 44% of the students are physiologic/health and 13% indicates health gain like future importance. Concludes that most of the practice was sportive, with techniques and basis without any critical reflection and develop concepts and important attitudes to the student’s present and future life not stimulating student’s autonomy in exercising. Therefore, the teachers should review the classes and targets in order the students don’t be mistaken in relation to the benefits and it’s read usefulness, are inexpressive and easily lost with interruption. Mainly because nowadays education target is to form critical and autonomous citizens.